Occupational toxicology study emphasizing the cytotoxic and mutagenic activity among workers exposed to gasoline - Lacerda, Lourran Paula (2015)
This article aimed to examine the cytotoxic and mutagenic effects of gasoline on exfoliated buccal mucosa cells among gas station attendants. The study was conducted through data survey, application of health questionnaires, and cytogenetic analysis, by applying the micronucleus test in oral mucosa cells. The population under study consisted of the Test Group, made up by 20 attendants, exposed to gasoline, in the city of Picos, Piauí, Brazil, and a Control Group, made up by 20 previously selected individuals. The results of this study showed that the frequency of micronuclei and cell death among individuals exposed to gasoline has been statistically significant (p < 0.001) when compared to the non-exposed group. This substance also induced cytotoxicity in the oral epithelium of exposed individuals (p < 0.001), by increasing the frequency of binucleated cells. These results are similar to those reported in the literature, regarding the mutagenic and cytotoxic effects of this additive. Furthermore, it was observed that none of the subjects in the Test Group has used personal protective equipment (PPE) and they do not know the toxic action of these compounds. Thus, there is a need for providing information to the exposed workers on the mutagenic and cytotoxic action of gasoline, emphasizing the importance of using PPE, in view of the risk posed to health that such exposure can bring.